A novel, rapid synthetic protocol for controllable sizes, conductivities and monomer units of soluble polypyrrole. (October 2015) - Mondal, Subrata; Sangaranarayanan, M.V.
Graphical abstract: Highlights: Rapid polymerization of pyrrole using NaNO2 and HNO3 . Controllable sizes, conductivities and monomer units of PPy spheres. Surfactant induces the solubility of PPy spheres. Selective detection of Cu 2+ and Hg 2+ ions using PPy solution. Abstract: We report a facile synthesis of polypyrrole spheres with controllable sizes, monomer units and conductivities using sodium nitrite and nitric acid in presence of the anionic surfactant sodium tetradecyl sulfate. The rapid synthesis of polypyrrole spheres was accomplished without employing any explicit oxidizing agents. The characterization of polypyrrole (PPy) is carried out using FTIR, XRD, SEM, TEM and TGA while the molecular weight is estimated from the MALDI TOF analysis. The precise tuning of various physicochemical properties is accomplished by altering the concentrations of sodium nitrite and is attributed to the in situ generation of NO2 . The size of the PPy spheres varies from 45 nm to 350 nm depending upon the concentration of NaNO2 . The dynamic light scattering studies provide mechanistic insights into the role of sodium nitrite in altering the pyrrole-incorporated micellar size of the surfactant, leading to different diameters of the PPy spheres. The surfactant-induced solubility of PPy is rationalized with the help of the X-ray diffraction patterns. The solution of PPy in dimethylsulfoxide has a remarkable ability of selectively detecting Cu 2+ and Hg 2+ among a host of other bimetallic ions, as inferred from colorimetry and UV–Visible absorption spectroscopy.